Some observations on the prawn fishery of Cochin - Suseelan, C; Rajan, K N; Nandakumar, G (Indian Journal of Fisheries, 2011)
Shrimp fishery bas played an important role in the socioeconomic growth of the Coastal people in recent years. Prawn fishing is practised throughout the 590 Ian coast line of Kerala, but in the past 3 -4 decades this .. industry has shown a remarkable development due to the mechanized fishing and processing of seafoods